2017
DOI: 10.1186/s12864-017-3845-9
|View full text |Cite
|
Sign up to set email alerts
|

Biological mechanisms discriminating growth rate and adult body weight phenotypes in two Chinese indigenous chicken breeds

Abstract: BackgroundIntensive selection has resulted in increased growth rates and muscularity in broiler chickens, in addition to adverse effects, including delayed organ development, sudden death syndrome, and altered metabolic rates. The biological mechanisms underlying selection responses remain largely unknown. Non-artificially-selected indigenous Chinese chicken breeds display a wide variety of phenotypes, including differential growth rate, body weight, and muscularity. The Wuding chicken breed is a fast growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Primers were commercially synthesized (Shanghai Shenggong Biochemistry Company P. R. China). Tissue homogenization, RNA isolation, and RT-qPCR were performed as previously described [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Primers were commercially synthesized (Shanghai Shenggong Biochemistry Company P. R. China). Tissue homogenization, RNA isolation, and RT-qPCR were performed as previously described [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Intensive selection in fast-growing broilers has resulted in increased muscularity and growth with additional adverse effects, including delayed development of the internal organs, which may be the potential cause of several metabolic disorders such as ascites or sudden death syndrome (Dou et al 2017). The birds in the current studies did not show any signs of these metabolic disorders, although the differences in internal organ size were detected.…”
Section: Discussionmentioning
confidence: 46%
“…We previously reported that the Daweishan mini chicken breed showed higher indexes of immune organs, especially for index of bursa, and higher expression of genes involved in specific immune traits in muscle tissue than the Wuding chickens [27]. The aim of the present investigation was to investigate the effect of body weight and age on the profiles of expression pattern of HDP genes in different immune organs and their association with innate immune function or adaptive immunity in chickens.…”
Section: Introductionmentioning
confidence: 89%
“…Tissue homogenization, RNA isolation, and RT-qPCR were performed as well as mRNA expression normalization as previously described[27,31,32]. Primer sequences for the target genes and their annealing temperatures.…”
mentioning
confidence: 99%